A Cognitive Psychological Explanation of Difficulties in Learning Katakana - Hossain, Muhammad Salim; Uddin, Muhammad Kamal (Dhaka University Journal of Linguistics, 2009)
Japanese is one of the difficult languages for the non-natives. Every year many Bangladeshi students enrolled in language schools to learn Japanese. However, many of them eventually fail to continue the course owing to the difficulties in learning Japanese. The present paper investigated which script of Japanese seems difficult for the learners. The findings indicated that Katakana seems to be difficult for the learners than the Hiragana. Two cognitive psychological explanations of the difficulties associated with in learning Japanese specially Katakana is offered and concludes by suggesting ways to reduce drops-out. Key words: Distinctive features, Hiragana, Katakana, Serial position effect DOI: 10.3329/dujl.v1i2.3721 The Dhaka University Journal of Linguistics: Vol. 1 No. 2 August, 2008 Page: 147-156